Value–Reflective Pedagogy (VRP–3F): A Conceptual Framework for Pancasila-Based Reflective–Value Learning - mujtahidin, mujtahidin (Universitas Trunojoyo Madura, 2025)
This conceptual article formulates the Value–Reflective Pedagogy (VRP–3F) and its operational counterpart, the Reflective–Value Learning Model (RVLM), as an integrated framework to strengthen reflection-based value education in elementary schools. The proposed framework addresses the gap between conventional reflective practices—often limited to administrative activities at the end of lessons—and the need for meaningful reflection that nurtures moral awareness, ethical reasoning, and value-oriented action. In alignment with current educational policies emphasizing deep learning and holistic character formation, the VRP–3F model serves as a pedagogical guide for teachers to embed reflective-value learning throughout the instructional process. Through a theoretical synthesis and reflective thematic analysis, the VRP–3F framework integrates Ki Hadjar Dewantara’s Among philosophy, Kolb’s Experiential Learning Theory, and Lickona’s Character Education model. The synthesis identifies three interrelated pillars of reflection: Feel (empathic–affective), Find (rational–cognitive), and Flow (practical–conative), forming a continuous cycle of value formation. The RVLM operational model elaborates these principles into seven core learning phases: value orientation, reality exploration, value reflection, value meaning construction, value appreciation, value enactment, and value reconstruction. The article concludes by recommending empirical implementation of VRP–3F and RVLM in value-based and deep-learning contexts to reinforce a reflective Pancasila pedagogy in Indonesian education.